THE RESEARCH OF THE INFLUENCE OF THE PRESSURE TO THE VALUES OF ELASTIC PARAMETERS OF GEOLOGICAL MEDIUM ON THE BASIS OF SEISMIC AND WELL DATA - Guliyev, H.; Aghayev, H.; Shirinov, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The questions on definition of fundamental elastic parameters on the basis of non-classic base model including the development of the software for preparation of 2D thin layered models of real environment and also the calculation of the sections of elastic parameters of the environment are considered.